Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1002/(sici)1097-4636(200005)50:2<160::aid-jbm10>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-deposited membranes for controlled release of antibiotic to prevent bacterial adhesion and biofilm formation

Abstract: Bacterial infection on implanted medical devices is a significant clinical problem caused by the adhesion of bacteria to the biomaterial surface followed by biofilm formation and recruitment of other cells lines such as blood platelets, leading to potential thrombosis and thromboembolisms. To minimize biofilm formation and potential device-based infections, a polyurethane (Biospan) matrix was developed to release, in a controlled manner, an antibiotic (ciprofloxacin) locally at the implant interface. One mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 24 publications
(15 reference statements)
2
55
0
Order By: Relevance
“…From research such as this, it is possible to foresee that plasma-based technologies could potentially be used for polymeric biomaterials in order to improve upon their bioactivity for use in biological environments. Plasma surface treatments have also been extensively used in the production of surfaces to control and investigate bacterial adhesion on numerous material types [148][149][150][151][152][153][154][155]. Plasma immersion ion implantation has been applied to surface treat poly(vinyl chloride) (PVC) [153] to successfully improve the antibacterial properties with specific regard to Staphylococcus aureus and E. coli.…”
Section: Figure 7: Sem Images Of (A) As-received and (B) Plasma Surfasupporting
confidence: 68%
“…From research such as this, it is possible to foresee that plasma-based technologies could potentially be used for polymeric biomaterials in order to improve upon their bioactivity for use in biological environments. Plasma surface treatments have also been extensively used in the production of surfaces to control and investigate bacterial adhesion on numerous material types [148][149][150][151][152][153][154][155]. Plasma immersion ion implantation has been applied to surface treat poly(vinyl chloride) (PVC) [153] to successfully improve the antibacterial properties with specific regard to Staphylococcus aureus and E. coli.…”
Section: Figure 7: Sem Images Of (A) As-received and (B) Plasma Surfasupporting
confidence: 68%
“…To circumvent electrostatic repulsion between film components, assembly was performed at pH 2.2, at which PAA carries no negative charge (pK a of PAA is B6.8). AFM measurements of film thickness by scanning the AFM tip over a razor scratch in the film confirmed that, similar to other clay-polyelectrolyte multilayers, 15,19 the dry thickness increased linearly with the number of deposited layers (Figure 1a), suggesting a low diffusivity of film components during deposition. The bilayer thickness for the MMT/PAA system of B15 nm is not unusual for polyelectrolyte/MMT, for which larger bilayer thicknesses have been reported, 32 with differential thicknesses of 11 ± 1 nm for clay and 4 ± 1 nm for PAA.…”
Section: Responsive Nanocomposite Assembliesmentioning
confidence: 99%
“…To alleviate this problem, a number of approaches 15 have been proposed to modify surfaces with polymer coatings that are anti-adhesive, 16,17 kill bacteria on contact, 18 elute antimicrobial compounds with time 19 or provide antibacterial protection through enzymatic degradation of a biofilm matrix. 20 The assembly of surface coatings via LbL deposition enables the inclusion of a broad range of components within conformal coatings and has been explored to construct contact-killing 21 or release-killing films.…”
Section: Introductionmentioning
confidence: 99%
“…Changing the deposition time length resulted in different coating thickness which, like the molecular weight of the drug, was found to influence the drug-release rate. A comparable approach was used on polyetherurethane onto which a plasma-deposited poly(butyl methyacrylate) membrane with controlled porosity was applied to control the release of ciprofloxacin (Hendricks et al, 2000). Adhesion and colonization of Pseudomonas aeruginosa was evaluated to assess the antimicriobial effectiveness.…”
Section: Regulation Of Drug Release By Barrier Layersmentioning
confidence: 99%